Making Áztlán : ideology and culture of the Chicana and Chicano movement, 1966-1977 - Gómez-Quiñones, Juan; Vásquez, Irene (Contextos (Albuquerque, N.M.), 2014)
"This book provides a long-needed overview of the Chicana and Chicano movement's social history as it grew, flourished, and then slowly fragmented. The authors examine the movement's origins in the 1960s and 1970s, showing how it evolved from a variety of organizations and activities united in their quest for basic equities for Mexican Americans in U.S. society"--Provided by publisher